LIVING WITH E-WASTE IN INDIA, ITS IMPACT ON ENVIRONMENT AND SCOPE OF MANAGEMENT - Dr. Nurjahan Rahmatullah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In the age of Information Technology, we all are aware of e-Waste or electronic waste, which comprises of discarded electronic devices like computers, laptops, cell phones, dvd players, cameras, televisions, refrigerators, copiers, printers, fax machines, stereos, play-stations, batteries and such other devices. India’s stride towards being a ‘Developed Nation’ can be witnessed from it increasing use of information technology, widespread use of electronic devices and mass appeal towards the next generation gadgets. Such maintenance of aura at the same time also produces large chunks of e-waste from such items. There is no doubt that the electronic devices come very handy to us and has become a part and parcel of our lives, yet, they also carry hazardous metals and chemicals in them like lead, zinc, nickel, flame retardants, barium, and chromium which if gets exposed in the environment can have tremendous impact on the biodiversity, wildlife and human beings. The impact of e-waste is slow but irreversible. The e-waste management should effectively deal with improper disposal of electronic items into the environment and should also encourage sustainable development of such technology which would have lesser impact on the environment if exposed to. It is time that Natural Disaster Management programmes should focus more on e-waste in India and should keep a strict control in the disposal of such wastes to make prevent an unimaginable menace that the e-waste can cause to the Nation and its population including the complete eco-system.